2007
DOI: 10.5301/jbm.2008.1872
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic localization of BAG-1 in leukoplakia and carcinoma of the tongue: correlation with p53 and c-erbB2 in carcinoma

Abstract: BAG-1 negativity in association with p53 and c-erbB2 positivity identified a subgroup of tongue cancer patients with an aggressive phenotype. Hence, an antiapoptotic protein, BAG-1, was found to be down-regulated in chewing-tobacco-mediated tongue carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Our results demonstrate an increase in BAG‐1 expression associated with the presence of perineural infiltration in OSCC. Some studies have suggested that analysis of BAG‐1 expression may be useful in establishing a prognosis for patients with oral SCCs and in predicting the metastatic potential of SSCs 30–33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate an increase in BAG‐1 expression associated with the presence of perineural infiltration in OSCC. Some studies have suggested that analysis of BAG‐1 expression may be useful in establishing a prognosis for patients with oral SCCs and in predicting the metastatic potential of SSCs 30–33 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that analysis of BAG-1 expression may be useful in establishing a prognosis for patients with oral SCCs and in predicting the metastatic potential of SSCs. [30][31][32][33] The protein Bcl-x has two isoforms, Bcl-xL and Bcl-xS, the former repressing cell death and the latter favouring cell death. We evaluated Bcl-x expression by using two different antibodies: one that does not distinguish between the short and long isoforms and an antibody against Bcl-xL.…”
Section: Bcl-2 Family Proteins In Oscc 311mentioning
confidence: 99%